2010
DOI: 10.1007/s11282-010-0055-4
|View full text |Cite
|
Sign up to set email alerts
|

A measure for quantifying the radiopacity of restorative resins

Abstract: Objective To evaluate the utility of the X-ray attenuation coefficient as a measure for quantifying the radiopacity of restorative resins at different exposure times and film speeds. Materials and methods Five restorative resins were made into disks, measuring 10 mm in diameter with thicknesses of 0.5, 1.0, 1.5, 2.0, and 2.5 mm. These resin disks, an aluminum step wedge, and a lead disk were placed on size 4 Ultraspeed Ò D and Insight Ò E/F films. X-ray parameters were 65 kVp, 10 mA, and 30-cm focus-to-film di… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
15
0

Year Published

2012
2012
2022
2022

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 10 publications
(15 citation statements)
references
References 10 publications
(20 reference statements)
0
15
0
Order By: Relevance
“…Unlike Gu et al11 and Sur et al,2 we determined that the setup changes had influenced the effect on the radiopacities of dental materials. Applying a charge-coupled device (CCD), Gu et al11 concluded that altering the exposure time and tube-target distance would not significantly change the radiopacity 11.…”
Section: Discussionmentioning
confidence: 86%
See 1 more Smart Citation
“…Unlike Gu et al11 and Sur et al,2 we determined that the setup changes had influenced the effect on the radiopacities of dental materials. Applying a charge-coupled device (CCD), Gu et al11 concluded that altering the exposure time and tube-target distance would not significantly change the radiopacity 11.…”
Section: Discussionmentioning
confidence: 86%
“…Applying a charge-coupled device (CCD), Gu et al11 concluded that altering the exposure time and tube-target distance would not significantly change the radiopacity 11. Moreover, using D, E, and F speed films and by means of the attenuation coefficient method, Sur et al reported that the different exposure times would not remarkably modify the radiopacity of dental materials 2. Notably, they did not consider target-tube distance as another confounder.…”
Section: Discussionmentioning
confidence: 99%
“…However, some researches have shown that under-processing occurs in a large portion of dental offices [10][11][12][13][14] , which may undoubtedly induce diagnostic errors. Lemke et al 15 , in their research, verified that the majority of professionals evaluated were performing radiographic overexposure, in order to under-process the radiographs afterwards, with the aim of reducing working time.…”
Section: Discussionmentioning
confidence: 99%
“…Grafts with the use of synthetic material have various benefits, such as availability, sterilization, abundance of donors, and reduced morbidity. This eliminates many of the deficiencies of autogenous grafts (SUR et al, 2011). Synthetic materials for these purposes may be metals, polymers, composites, ceramics, and glass.…”
Section: Discussionmentioning
confidence: 99%
“…Synthetic materials for these purposes may be metals, polymers, composites, ceramics, and glass. Zirconia is a frequently used synthetic material at present, particularly in the fields of medicine and dentistry, promoting functional reestablishment with prosthetic parts in hip and femur prostheses, dental implants, and copings (AL RUHAIMI, 2001;SUR et al, 2011) as it is a highly biocompatible and inert biomaterial, like ceramics (HISBERGUES et al, 2009).…”
Section: Discussionmentioning
confidence: 99%